PENGARUH MODAL, TENAGA KERJA, HARGA DAN LAMA USAHA TERHADAP PENDAPATAN UMKM KULINER DI KOTA SURAKARTA - Wafiqotul Luthfiyah; Arif Nugroho Rachman (JURNAL ILMIAH PENELITIAN MAHASISWA, 2023)
The purpose of this study was to determine the effect of capital, labor, prices and length of business on culinary MSME income in Surakarta. This study uses a non-probability technique (purposive sampling), which is a sampling technique by establishing certain criteria set by the author. This study uses a type of quantitative research. The population in Culinary SMEs in Surakarta City is 1,729 based on data from the Surakarta Cooperative Service, with a sample of 95 samples. Data analysis using Multiple Linear Regression Analysis. This research was assisted by the SPSS application analysis tool version 26. The results of this study indicate that capital and labor have no significant effect on income. While the price and length of business have a significant effect on income.